The Effect of Duration of Amidation of Fatty Acids with Diethanolamine on the Surfactant Properties. Issue 3 (4th December 2018) - Yanovsky, Viacheslav A.; Andropov, Mikhail O.; Fakhrislamova, Regina S.; Churkin, Ruslan A.; Minaev, Konstantin M.; Yanovskaya, Elena A.
Abstract: The effects of the duration of direct amidation of fatty acids (FA) with diethanolamine on the composition of the products obtained, their surface‐active properties, and ability to stabilize water‐in‐oil emulsions are studied using the example of tall oil distillate. A certain range of synthesis time that corresponds to the maximum content of diethanolamides in the reaction products, and, as a consequence, the highest surface‐active and emulsifying properties of the products is shown to exist. An increase in the synthesis duration time leads to a deterioration of these properties due to accumulation of the products of secondary reactions. A new mechanism of the amidation process that includes secondary transformations of diethanolamine and its condensation products with FA into 1, 4‐ bis (2‐hydroxyethyl)piperazine derivatives is proposed. The structures of by‐products are confirmed using high‐performance liquid chromatography‐mass spectrometry (HPLC–MS), infrared (IR), and nuclear magnetic resonance (NMR) spectroscopy methods. It is concluded that the acid value of the product as well as the amount of water released during the synthesis cannot serve as a reliable criterion for completion of the process.